2015
DOI: 10.1136/jech-2015-205623
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing the sources of the Asian mortality advantage in the USA

Abstract: Background Asian-Americans outlive whites by an average of nearly 8 years. By determining the sources of the Asian mortality advantage, we can pinpoint where there is the greatest potential for raising the life expectancy of whites and other groups in the United States. Methods Our analyses include all Asian and white deaths in the United States between 2006 and 2010, from the Center for Disease Control (CDC). Using the International Classification of Diseases (version 10), we code causes of deaths into 19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Loss to followup, which contributes to inflated survival estimates, may occur because of the return of immigrants with serious illnesses to their countries of origin to die, a phenomenon known as the salmon bias [47,48]. However, studies thus far indicate that salmon bias has limited impact on Asian American survival, likely due to travel being too distant and time-consuming for gravely ill individuals to undertake [49,50]. Lastly, some important covariates, such as residual tumor category, comorbidities, and postoperative complications, are critical factors impacting gastric cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Loss to followup, which contributes to inflated survival estimates, may occur because of the return of immigrants with serious illnesses to their countries of origin to die, a phenomenon known as the salmon bias [47,48]. However, studies thus far indicate that salmon bias has limited impact on Asian American survival, likely due to travel being too distant and time-consuming for gravely ill individuals to undertake [49,50]. Lastly, some important covariates, such as residual tumor category, comorbidities, and postoperative complications, are critical factors impacting gastric cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found selective reverse migration to be true among Mexican migrants in the USA, with higher probabilities of Mexican migrants in poor health to return home (and lower probabilities of return in improving health). 42 Statistical immortality may differ by Asian subgroup, given possible differences in ease of return migration. For instance, it may be easier for US citizens to return migrate to Japan rather than China, given the more favourable visa and citizenship requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The age-incidence decomposition isolates these two sources of change. In the twofactor approach, used in Acciai, Noah, and Firebaugh (2015) and in Firebaugh et al (2014), the age component for cause c is as follows:…”
Section: The Age-incidence Decomposition Methodsmentioning
confidence: 99%
“…By separating the incidence and age components we determine whether change in life expectancy is occurring because people are dying of different causes, or because they are dying of the same causes but at different ages (Acciai, Noah, and Firebaugh 2015;Firebaugh et al 2014). Change in life expectancy is due to change in death rates, and age-incidence decomposition reveals the locus of the death rate changes that are driving the change in life expectancy.…”
Section: Age Componentmentioning
confidence: 99%
See 1 more Smart Citation